Analisis Nilai Tambah Jipang pada Usaha “Gareng Lutfi” di Desa Moolo Indah Kecamatan Tinanggea - Santoso, Dwi; Iswandi, R. Marsuki; Abdullah, Weka Gusmiarty (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
This study is motivated by jipang cake which still uses rice as a raw material in its production process is found in the home industry, so it is still unknown how much-added value is cultivated. This study aims to determine the added value obtained from processing into jipang cake in the business of